Pengaruh Digitalisasi terhadap Masyarakat Suku Baduy dalam Mempertahankan Adat dan Tradisi Leluhur - Aura Andriani; Munawaroh Munawaroh (Master Manajemen, 2025)
The purpose of this study was to determine the impact of digitalization and the efforts of the Baduy community in preserving and maintaining local culture in the current digital era. The Baduy community is located in Kanekes Village, Leuwidamar District, Lebak Regency, Banten Province. The Baduy community strongly adheres to traditional values ​​and has very little interaction with modern technology, as time goes by digital technology has begun to enter their society. The research method used is a qualitative approach with data collection techniques through open questionnaires and in-depth interviews. The questionnaire was designed to reveal the perceptions of the Baduy Tribe community regarding the use of digital technology and its impact on their cultural values. The data collected was analyzed using thematic analysis to identify patterns and trends related to the impact of digitalization on the preservation of customs.